Rekayasa Mesin Pemotong Batang Padi dengan Mata Potong Berbentuk Piringan - Rianto, Ari; Suhendra, Suhendra; Nopriandy, Feby; Erwin, Erwin (Universitas Muhammadiyah Metro, 2024)
Proper harvest handling has an influence in reducing yield losses. Harvesting activities must be carried out at the right time, using the correct tools or techniques and implementing an appropriate harvest system. The harvesting machines currently on the market are large-scale harvesting machines, relatively large in size and very heavy. Based on these problems, research was carried out aimed at design, construction and testing a small rice stalk cutting machine that has high mobility. The method in this research includes the stages of design, construction, testing and data analysis. The data measured in the test are movement speed and cutting capacity. Based on design and construction results, the rice stalk cutting machine has specifications for length 82 cm, width 62 cm, height 95 cm, drive motor power 1.25 kW, and cutting blade rotation speed 1,900 rpm. The test results show that the average cutting forward speed is 0.330 m/s and the average cutting capacity is 0.132 m2/s.